2016
DOI: 10.1016/j.jvs.2015.08.117
|View full text |Cite
|
Sign up to set email alerts
|

Outcome comparison between open and endovascular management of axillosubclavian arterial injuries

Abstract: In our experience with axillosubclavian arterial injuries, ER was associated with improved mortality and lower complication rates. Patient follow-up demonstrates an acceptable reintervention rate after ER. Further multicenter prospective evaluation is warranted to determine long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 25 publications
(36 reference statements)
0
59
0
7
Order By: Relevance
“…In a comparison of outcomes after endovascular repair and open operative repair, Branco et al reported a statistically significant decrease in mortality (5.6% versus 27.8%, respectively; P = 0.04). The authors also reported a lower complication rate with the endovascular approach [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparison of outcomes after endovascular repair and open operative repair, Branco et al reported a statistically significant decrease in mortality (5.6% versus 27.8%, respectively; P = 0.04). The authors also reported a lower complication rate with the endovascular approach [5].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the United States the most common mechanism causing this type of vascular injury is a gunshot wound [4]. Subclavian artery injuries are associated with a high mortality and despite advances of modern medicine remain extremely lethal injuries [5]. Management is particularly challenging due to anatomic location with the proximal third of the subclavian artery located within the thoracic cavity, hindering exposure, and because of the numerous delicate neurovascular structures in the vicinity, increasing the risk of collateral damage during repair or associated injuries [6].…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular procedures have overcome the problems associated with open exposure procedures and are being adopted more often. In the last 10 years, the rate of trauma-associated deaths has increased faster than that of deaths among the general population [5-7] , and penetrating trauma accounts for a significant fraction of these deaths. Traumatic artery injuries, such as injuries in the axillosubclavian region, have high rates of morbidity and mortality 5,6)] , This high rate of morbidity and mortality could be explained because of the need for extensive dissection required in such region on top of the nature of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…The Endovascular Skills for Trauma and Resuscitative Surgery Working Group reported that endovascular procedures were successful in 96.9% of patients. [4] Branco et al [5] analyzed the positive impact of endovascular therapy in patients with sustained axillosubclavian arterial injuries and found a statistically significant difference in mortality: 5.6% for endovascular repair versus 27.8% for open repair. These authors also showed that patients treated with endovascular repair tended to have lower rates of complications, particularly surgical-site infections and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the medical literature from 1990 to 2012 identified ten axillary artery injuries undergoing endovascular stenting with promising early results but limited data on late follow-up [34]. In a recent retrospective study from two high-volume trauma centers, endovascular intervention of axillo-subclavian arterial injuries was associated with improved survival and lower complication rates compared to open repair using propensity score matching [35]. Case series has previously shown shorter operative time and less blood loss with an endovascular approach in selected patients with an arterial subclavian-axillary injury [36,37].…”
Section: Axillary Vesselsmentioning
confidence: 99%